Design and Implementation of Sorting Waste Bins as an Integrated Waste Management System in the School Environment - Hisyam Ihsan; Fajar Arwadi; Muhammad Ammar Naufal; Riswansyah; Ahmad Israk; Lutfiah (LPP Chani, 2025)
This program aims to develop an effective waste management system in schools to increase environmental awareness. A segregated waste bin system with color categorization (green, yellow, nir, red) is implemented to make it easier to sort waste, especially organic and inorganic waste. This program is carried out based on needs analysis, system design, implementation and effectiveness evaluation. The results show an increase in students' waste sorting accuracy of 75% and increased awareness of the environment. However, challenges such as consistency of sorting, maintenance and changing habits still need to be addressed. This program recommends ongoing maintenance and education to increase the effectiveness of waste management systems in schools. In this way, it is hoped that environmental awareness and the quality of the school environment can be improved. This program contributes to the development of waste management systems in schools.